2022
DOI: 10.3389/fnut.2022.1008584
|View full text |Cite
|
Sign up to set email alerts
|

Association between blood selenium levels and gestational diabetes mellitus: A systematic review and meta-analysis

Abstract: IntroductionThe association between blood (serum or plasma) selenium concentrations and gestational diabetes mellitus (GDM) has been evaluated in some studies. However, the reported findings are debatable, and only case-control and cross-sectional studies were included.ObjectiveThis research aimed to assess the association between blood selenium levels and GDM by analyzing existing literature. To provide a reference for the prevention and treatment of GDM, we included prospective studies which are not included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…In the current study there was an overall trend for a positive association of SELENOP with T2D in men, in agreement with the mechanistic studies for SELENOP and most of the observational human studies [ 22 ]. In line with the evidence of an inverse association of Se status with gestational diabetes [ 42 ], there was no association observed in women.…”
Section: Discussionsupporting
confidence: 54%
“…In the current study there was an overall trend for a positive association of SELENOP with T2D in men, in agreement with the mechanistic studies for SELENOP and most of the observational human studies [ 22 ]. In line with the evidence of an inverse association of Se status with gestational diabetes [ 42 ], there was no association observed in women.…”
Section: Discussionsupporting
confidence: 54%
“…Low serum selenium levels may contribute to the development of GDM, and selenium supplementation may reduce the risk of GDM. [107–112]…”
Section: Trace Elementmentioning
confidence: 99%
“…[106] Low serum selenium levels may contribute to the development of GDM, and selenium supplementation may reduce the risk of GDM. [107][108][109][110][111][112] Meta-analyses suggest that magnesium deficiency contributes to GDM. [113][114][115] Prospective studies have also shown that magnesium deficiency contributes to the development of GDM.…”
Section: Vitaminmentioning
confidence: 99%